Radiofrequency Ablation of Hepatocellular Carcinoma: A Literature Review - Yasunori Minami; Masatoshi Kudo (International Journal of Hepatology)
Radiofrequency ablation (RFA) of liver cancers can be performed safely using percutaneous, laparoscopic, or open surgical techniques, and much of the impetus for the use of RFA has come from cohort series that have provided an evidence base for this technique. Here, we give an overview of the current status of radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC), including its physical properties, to assess the characteristics that make this technique applicable in clinical practice. We review the technical development of probe design and summarize current indications and outcomes of reported clinical use. An accurate evaluation of treatment response is very important to secure successful RFA therapy since a sufficient safety margin (at least 0.5 cm) can prevent local tumor recurrences. We also provide a profile of side effects and information on the integration of this technique into the general management of patients with HCC. To minimize complications of RFA, physicians should be familiar with each feature of complication. Appropriate management of complications is essential for successful RFA treatment. Moreover, adjuvant therapy, such as molecular targeted therapies following curative therapy, is expected to further improve survival after RFA.